Aprendendo a aprender: comece pela capa - Biondo, Guiomar Josefina [UNESP]; Brito, Sônia de [UNESP] (My University, 2011)
From the book of Newton Duarte (2000) Vigotysky and “Learning to Learn”, you can make a compelling reflection of the cover, a masterpiece of the artist Max Ernst, “Birds, too: Bird-Snake and Scarecrow” by 1921 (in Bischoff, 1993) and the phrase “Learning to Learn”. Compare and interpret the theme of Vygotsky with the picture is our purpose, because look at the painting on the surface of the cover is meaningless by itself, is necessary to seek a dual mechanism of visual perception on what it represents. It is a metaphor. Such explicit representation abroad and, by analogy, implicitly synthesizes the inside of a slogan that has become a symbol of the innovative teaching positions

Do livro de Newton Duarte (2000) Vigotysky e “Learning to Learn”, Pode-se ter uma profunta reflexão a respeito da capa, uma obra-prima do artista Max Ernst, “Birds, too: Bird-Snake and Scarecrow” by 1921 (in Bischoff, 1993) and the phrase “Learning to Learn”. Compare e interprete o tema de Vygotsky com a imagem é nosso propósito, por que apenas olhar na figura de uma capa não tem sentido. É necessário enxergar um mecanismo duplo de percepção visual do que ela representa. É uma metáfora. Uma representação explícita e, por analogia, implicitamente sintetiza o interior de um slogan que ten se tornado um símbolo de posições de ensino inovadoras.
Learning to learn: Start by its cover
Keywords: Max Ernst; Cover interpretation; Learning to learn; Max Ernst; Interpretação das capas; Aprendendo a aprender